2012
DOI: 10.1111/j.1447-0349.2012.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in health care for the somatic health of outpatients with severe mental illness

Abstract: The physical health of outpatients with severe mental illness (SMI) can be improved by changes in the health-care system. Analysis of current practice is necessary to develop these strategies. We compared the number of somatic health problems of outpatients with SMI with the frequency of consulting a general practitioner (GP). This was a cross-sectional study based on interviews, and records from the GP and the pharmacy. We checked whether Dutch community pharmacies had complete and correct information about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…As a consequence, they have to make extra appointments, which might give them stress. Furthermore, it should be noted that there is a subgroup of patients, which seldom visits the GP even though they experience physical health problems [16]. …”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, they have to make extra appointments, which might give them stress. Furthermore, it should be noted that there is a subgroup of patients, which seldom visits the GP even though they experience physical health problems [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the problems detected by the somatic health screening may not have been presented to the GP by the patient. In another study, we found that patients with SMI who had less than annual contact with their GPs often had clinically relevant somatic health problems (van Hasselt et al., ). Secondly, it is possible that the GP is aware of the risk, but did not add this as a diagnosis in the medical file.…”
Section: Discussionmentioning
confidence: 96%
“…A cross‐sectional descriptive study design was used, as described in detail elsewhere (van Hasselt et al., ). Participants included 118 patients with SMI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that improving access and provision of physical health care in mental health services would be of significant benefit to the physical health of consumers with SMI (Happell, Scott, & Platania-Phung, 2012a;Lambert, 2009;Lawrence & Kisely, 2010;van Hasselt et al, 2013) and may improve their quality of life and pathways to recovery. Improving cardiovascular care requires a 'whole system' approach, including mental health care (Hardy & Thomas, 2012;Lawrence & Kisely, 2010;Stanley & Laugharne, 2012).…”
Section: Introductionmentioning
confidence: 98%